The Death of Whiggery: Lower-Canadian British Constitutionalism and the tentation de l’histoire parallèle - McCulloch, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1991)
AbstractThe Constitutional Act of 1791 was sought to create in Lower Canada a community whose social and political values reflected the basic assumptions of late-eighteenth-century Whiggery. These included representation of interest rather than of individuals, the importance of the "due" weight of property, and the organic nature of the British constitution. These values of "Liberty and Property" constituted the focus of the emotional and cultural image of the British Constitution. For the British Lower Canadians of the 1830s, these values were not fossilised remnants. Rather, they formed a coherent framework that made legitimate their conflict with the French-Canadian majority for control over politics. The influence of organised Constitutionalism did not disappear with the Act of Union of 1841. In the opening years of the union, anglophones identified with the Constitutionalist party which dominated both opposition and government in Canada East. They remained an influence until midcentury. Indeed, the final disintegration of Constitutionalism as a defensible basis for British Lower-Canadian politics was not the result of the inevitable triumph of La Fontaine's Responsible Government. Because they strongly identified, not simply with Britain, but with specific elements of British society, English-speaking Lower Canadians responded to changes in British political society. “La tentation de l'histoire parallèle” ensured that the Irish Repeal agitation and the Free Trade campaign would disrupt the assumption of a united British "interest." After the 1840s, the disproportionate power of British-Canadian élites in Lower Canada was based on their influence among the leaders of political parties rather than a collective identity rooted in the values of ''Whiggery.''